2020 European guideline on the management of genital molluscum contagiosum. (2nd September 2020) - Edwards, S; Boffa, MJ; Janier, M; Calzavara‐Pinton, P; Rovati, C; Salavastru, CM; Rongioletti, F; Wollenberg, A; Butacu, AI; Skerlev, M; Tiplica, GS
Abstract: Molluscum contagiosum is a benign viral epidermal infection associated with high risk of transmission. The guideline is focused on the sexually transmitted molluscum contagiosum. The diagnosis is clinical with characteristic individual lesions, termed 'mollusca', seen as dome‐shaped, smooth‐surfaced, pearly, firm, skin‐coloured, pink, yellow or white papules, 2 ‐ 5 mm in diameter with central umbilication. Dermoscopy may facilitate diagnosis. Therapeutic options are numerous, including physical treatments (cautery, curettage and cryotherapy), topical chemical treatments (e.g. podophyllotoxin and imiquimod) or waiting for spontaneous resolution in immunocompetent patients. In pregnancy, it is safe to use physical procedures (e.g. cryotherapy). Immunosuppressed patients develop severe and recalcitrant molluscum lesions that may require treatment with cidofovir, imiquimod or interferon. Patients with molluscum contagiosum infection should be offered to be screened for other sexually transmitted infections.